Experimental Investigation of the Essential Information in the Part of Remarks of Operation Manual to Support Novice Plant Operators. Issue 19 (2016) - Matsubara, Takashi; Gofuku, Akio; Sugihara, Taro
Abstract: Operation manuals are used to support plant operators in order to reduce human errors and to ensure the quality of operation independent on the skill of operators. However, there are some troubles happened by the causes of problems in operation manuals. The authors analyzed the reported trouble cases happened in petroleum and nuclear industries due to the problems in operation manuals. The analyses revealed that most of the trouble cases were caused by insufficient information in the part of remarks in operation manuals. This means that novice operators need some more information in addition to that of operation purpose and goal, operation step names, the order of operation steps, and concrete operation actions. This study investigates experimentally the influence of insufficient information in the part of remarks on the performance of novice plant operators using an artificial and semi-scaled boiler type power generating plant. Several categories of information described in the part of remarks are identified. Then, two types of operation manuals are prepared. The one describes all information in the part of remarks. Another type has some missing information that may support operators. The experimental results show that the usage of the operation manuals describing all information has much effect to decrease operation risk and the rate of omitting an operation action. However, the operation time to complete a task becomes longer. The results also suggest that sufficient description of the information has little effect on the understanding of operations.